Development of a preliminary ‘Tourgital’ acceptance framework: an experience of tourist in Seremban district - Zulkifli, Nordayana; Abdullah, Siti Nur Fadzilah; Ku Ahamad, Ku Nurul Atiqah; Mohd Amin, Farah Azaliney; Dzulkifli, Nur Nadia; Mohd Beta, Raja Mayang Delima (2023)
The current study has set a goal, that is to create a preliminary framework for evaluating Tourgital's acceptance as a digital platform that will improve visitors' experiences in the Seremban neighborhood. The preliminary framework of Tourgital’s acceptance is a unique concept that can be implemented by other researchers to study it more deeply and able to boost tourism research. A survey and semi-structured interviews with tourists were part of the study's mixed-methods methodology. The results indicate that tourists have a high level of acceptance for the Tourgital platform, with the vast majority stating a willingness to utilize it in the future. Perceived usefulness, perceived ease of use, perceived enjoyment, and trust are the four main components of the framework. To improve the experience of visitors and raise their satisfaction levels, the preliminary Tourgital acceptance framework can be utilized as a guide for future tourism field research and tourism digital platform development. the aims of this study are to determine the level of clarity towards the digitalization of information post-Covid 19, to develop a preliminary ‘Tourgital’ framework for the tourism industry in Seremban District post-Covid 19 and to analyze the impact of ‘Tourgital’ in Seremban District post-Covid 19. The researcher will discuss the approach they intend to use in order to obtain valid and reliable data. There are a number of topics that will be covered, including the procedure, action plan, sampling, and data interpretation. The conceptualization and operationalization of these variables for the research will also be stated by the researcher. The tourists while visiting the Seremban district. Both TAM and UTAUT models can be useful for the development of the Tour Digital acceptance framework. In turn, the development of an acceptance framework for the Tour Digital system in the Seremban District can benefit both tourists and tourism stakeholders. It is worthy of mention that the presentation of credible information, security measures, and positive reviews can help establish trust in the Tour Digital system, or better known as the “TOURGITAL” concept. A preliminary framework called a journey map has been constructed to conclude the objectives that have been focused on by referring to the results that were collected from the respondents and analysis data. The framework as shown in Figure 3.